The Effect of Sports Sponsorship Activities on the Brand Equity: A Study on Sports Clubs and Their Fans in Jordan - Al-Nsour, Iyad A. (Jordan Journal of Business Administration, 2022)
This study aims to investigate the impact of sports sponsorship activities on the brand equity in the minds of the Jordanian sports audience, in addition to determining the statistical differences in the level of awareness of sports sponsorship activities as well as the brand equity variables according to some demographic variables. The research population consisted of two sub-groups which are the sports clubs and their fans in the city of Amman. The purposive sampling technique was used. The unit of analysis in the sports clubs is represented in the athletes, administrative and technical employees with a sample size of 50 persons, while the audience is represented in the followers of the Jordanian Professional Football League for the 2020/2021 season with a sample size of 385. The study found that sports sponsorship activities have a strong positive statistical effect on the brand equity in the minds of the Jordanian sports audience. It was also found that there is a negative relationship between the brand equity and the age of the sports audience, while a positive relationship between awareness of sports sponsorship activities and age was proved. The other demographic variables were not statistically significant. Finally, the study suggested a set of recommendations that enhance the sports sponsorship activities in the sports market, such as regulating sports sponsorship contracts and stimulating the private sector to adopt these contracts in Jordan.